Economic Evaluation and Potential Assessment of Solar Water Heaters in Urban Ghana A Contribution to an Environmentally Sustainable Framework - Amarvie, F.D.K. (University of Ghana, 1996)
This project work describes the different methods of analyzing the economics of a solar water heating system to determine its economic viability and potential in Ghana. The economic variables in relation to cost that were considered in the analyses are the annual cost of owning the collector, storage unit and associated controls, the annualized life-cycle cost (ALCC) of operating the system, the yearly cost of maintenance, life-cycle savings (LCS), life-cycle cost (LCC), the payback period (PBP). Based on cost analysis, solar water heaters were found more economical than the use of electric water heaters. A survey conducted in parts of Accra to determine the awareness of the use of solar water heaters, and the affordability of solar water heaters in Ghana, revealed that solar water heaters can be afforded by commercial users (restaurants, hotels, hospitals) and very few private individuals in the medium and high income groups. Critical evaluation of income and expenditure patterns of potential end users revealed that the expenditure pattern of all the income groups is much higher than their corresponding income levels. A further analysis of the income and expenditure pattern revealed that if all the income is to be used in the installation of a solar water heater, for a family of four in low, medium and high income groups with average income of one hundred and twenty-five thousand, two hundred and fifty thousand, and three hundred thousand cedis respectively, it would take ten, six, and five years respectively to purchase a solar water heater. An economic and financial viability analyses (see appendices C and D) of a thermosyphon solar water heater were made using an f-chart simulation program, and technical viability using eurosol simulation program for thermal solar water heating systems. The results of the economic analyses revealed that for such a system with an economic lifetime of ten years, the marginal investment is profitable over the economic lifetime and a payback period of eight years.
Thesis (MPhil.) - University of Ghana, 1996
Keywords: Solar Water Heaters; Solar Power; Thermosyphon